Torturous Dialogues: Geographies of Trauma and Spaces of Exception - Perera, Suvendrini (Routledge: Taylor and Francis Group, 2010)
How are suffering, damage and disaster produced and made visible across different sites, and how are they made to count, to matter? This essay considers certain philosophical, historical and geopolitical coordinates that locate trauma and disaster in the context of the Indian Ocean tsunami of 2004. Trauma in its various significations – the banal, the aesthetic, the philosophical, the medicalized, the political, the pathologized – is an essential form of currency in the torturous dialogues that make, define and delineate the contours of disaster, damage and suffering. These are constitutively geopoliticized, as they are racialized and gendered, processes. Trauma is a medium that enables dialogue and exchange; it is eminently transactable, mobile and adaptable in its circulation between the refugee camp and the disaster victims' camp; it ramifies, with uneven meanings and effects, across and between subjects, scenes, sites, practices and relations. This essay considers the geopolitics of the tsunami as a globalized trauma-event and asks how the biopolitics of trauma, as a set of institutionalized practices for managing and ordering the life and health of populations, plays out across the necropolitical terrain of global inequality and in relation to those it locates as bare life.